CHIME/Fast Radio Burst Discovery of an Unusual Circularly Polarized Long-period Radio Transient with an Accelerating Spin Period - Fengqiu Adam Dong; Kaitlyn Shin; Casey Law; Mason Ng; Ingrid Stairs; Geoffrey Bower; Alyssa Cassity; Emmanuel Fonseca; B. M. Gaensler; Jason W. T. Hessels; Victoria M. Kaspi; Bikash Kharel; et al. (The Astrophysical Journal Letters)
We report the discovery of CHIME J1634+44, a long-period radio transient (LPT) unique for two aspects: it is the first known LPT to emit fully circularly polarized radio bursts, and it is the first LPT with a significant spin-up. Given that high circular polarization (>90%) has been observed in FRB 20201124A and in some giant pulses of PSR B1937+21, we discuss the implications of the high circular polarization of CHIME J1634+44 and conclude its emission mechanism is likely to be “pulsar-like.” While CHIME J1634+44 has a pulse period of 841 s, its burst arrival patterns are indicative of a secondary 4206 s period, probably associated with binary activity. The timing properties suggest it has a significantly negative period derivative of $\dot{P}=-9.03(0.11)× {10}^{-12}$ s s ^−1 . Few systems have been known to spin up, most notably transitional millisecond pulsars and cataclysmic binaries, both of which seem unlikely progenitors for CHIME J1634+44. If the period was only associated with the spin of the object, then the spin-up is likely generated by accretion of material from a companion. If, however, the radio pulse period and the orbital period are locked, as appears to be the case for two other LPTs, the spin-up of CHIME J1634+44 could be driven by gravitational-wave radiation.